Inflammation in Depression - Rahmawati, Novi Agung; Karimah, Azimatul; Amin, Mustafa M (Jurnal Psikiatri Surabaya, 2021)
Depression is a chronic condition that imposes a substantial burden of disability globally. Three principal neurotransmitters (norepinephrine (NE), dopamine (DA), and serotonin (5-HT)) implicated the pathophysiology and treatment of depression. Clinical studies have found a signiï¬cant association between numerous pro-inï¬‚ammatory cytokines with depressive symptoms, endocrine, and neurotransmitter systems. Here, we detail our current understanding about the role of inï¬‚ammation in depression, the mechanisms that are involved, and show how it is possible to innovate and develop new therapeutics of depression in the ï¬eld of neuroinï¬‚ammation.